INVESTIGATION OF THE NEUROPROTECTIVE EFFECT OF LINAGLIPTIN AND CELIPROLOL IN RESERPINE-INDUCED OROFACIAL DYSKINESIA AND ROTENONE-INDUCED NEURODEGENERATION IN RATS - NADE, VANDANA S.; MARDHEKAR, VISHAL Y.; BHOYE, UNNATI R.; KAWALE, LAXMAN A. (International Journal of Current Pharmaceutical Research, 2020)
Objective: Linagliptin, an anti-diabetic agent, proven to play an important role in regulating neuronal plasticity and reduce apoptosis and neuroinflammation by activating downstream AMPK/Sirt 1 pathway, which protects mitochondrial function and suppresses intracellular ROS accumulation and shows antioxidant action. Celiprolol, a β-1selective adrenoceptor blocker used as an anti-hypertensive agent, possesses a direct scavenging activity on oxygen radicals with antioxidant properties. The current study was designed to investigate the combined neuroprotective effect of linagliptin and celiprolol. Methods: Wistar rats of either sex were divided into different groups (n = 6). Eight groups each for Reserpine induced orofacial dyskinesia model and Rotenone induced neurodegeneration model to mimic Parkinson’s like conditions and treated or not with different doses of linagliptin and celiprolol. 24 h after the last dose, animals were subjected to behavioral, biochemical and histopathological evaluations. The data were analyzed by ANOVA and Bonferroni multiple comparison test. Results: Reserpine treatment increased VCMs, tongue protrusion and decreased locomotor activity. Rotenone treatment decreases the motor activity and exploratory ability of the animals. Reserpine as well as rotenone treatments decrease catalase, GSH, SOD and increase the LPO levels as compared to sham group animals. Reserpine and rotenone also showed the presence of ghost cells and vacuolated cytoplasm. Linagliptin and celiprolol alone as well as in combination normalized the behavioral, biochemical and histopathological complications. Conclusion: Linagliptin and Celiprolol showed neuroprotection by antioxidant activity as well as improved reserpine and rotenone-induced behavioral deficits. Both drugs have tenacious potential and can be used clinically with some further investigations.